HEURISTIC THINKING ON DATA VISUALIZATION BASED ON DASHBOARD CASE STUDIES AT NATIONAL HOSPITAL SURABAYA - R Hendarto Oktavianus; Dedhy Sulistiawan (Universitas Islam Kuantan Singingi, 2021)
Dashboard-based data visualization has various information is an option for presenting data is expected to support decision making. The ease of the dashboard isn't perfect, but it also has weakness. The nature of heuristic thinking makes users behave inconsistent with the rational decision-making process tobe an important issue. This study was conducted to explain the heuristic thinking behavior phenomenon from dashboard-based data visualization in the decision-making process. A qualitative approach is used with procedures and data collection based on interview techniques, observation and literature study. Data were observed from the National Hospital, Surabaya. The result is there is a bias in seeing data in a visual form, someone will tend to simplify the decision-making process. The contribution of this study is heuristic thinking on dashboard-based data visualization which can lead users to make irrational decisions.